Contenido de compuestos nitro en diferentes especies del genero Astralagus - Rodenas, I.=700 1 Caáinello, M.
(Es, En)
ilus., 14 ref.
Keywords: ASTRAGALUS; LEGUMINOSAS; COMPUESTOS NITROSOS; ESPAÑA; ALGARROBO